Imago theraphy - Love, Pat (Boston, MA : Allyn & Bacon Professional)
This video series features the theories of family therapy and counseling with real clients, real issues and today's leading family therapist
Editor, Patricia Quinlin
Moderator by Jon Carlson, Diane Kjos
Keywords: Family psychotherapy